ANALISIS KESENJANGAN DAN STRATEGI SOLUSI DALAM MENGHADAPI KRISIS PENDIDIKAN DI INDONESIA - Suryadi Mikael; Mathilda Sunta; Haikal Aprilianza; Rachmah Ayu Safitri; Dr. Yulius Yohanes, M.Si (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Indonesian education system is facing a significant crisis that hinders national development and equity. This study identifies the root causes of the education crisis, including infrastructure disparity, unequal access, curriculum irrelevance, and teacher competency issues. By reviewing relevant literature and national data, this paper proposes a multi-sectoral strategy to resolve educational inequality and improve quality. This research finds that a decentralized education policy combined with focused investment in rural education infrastructure, digital learning platforms, and teacher capacity building programs could create a more equitable and effective education system. The paper concludes by recommending policy reforms and future research directions. Keywords: education crisis, inequality, Indonesia, teacher competency, education reform